2012
DOI: 10.1136/tobaccocontrol-2011-050397
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the vector in order to plan effective tobacco control policies: an analysis of contemporary tobacco industry materials

Abstract: Background This paper builds on tobacco document research by analysing contemporary materials to explore how the global tobacco market has changed, how transnational tobacco companies (TTCs) are responding and identify the implications for tobacco control. Methods Analysis of a variety of materials including tobacco company annual reports, investor relations materials, financial analyst reports, market research reports and data. Findings Once China, where TTCs have little market share, is excluded, global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 39 publications
1
71
0
Order By: Relevance
“…17 It is also consistent with research in the US, with young adult menthol smokers suggesting that capsule cigarettes would attract beginners, 10 and research in Mexico, with adolescents found to be more interested in trying cigarettes with capsules than without them. 9 With innovation fundamental to value growth for tobacco companies and younger people most receptive to such innovation, 18 the capsule segment has been a welcome success story for tobacco companies.…”
Section: Yum That Is Not Going To Help Me Quit (16-17 Female C2de)mentioning
confidence: 99%
“…17 It is also consistent with research in the US, with young adult menthol smokers suggesting that capsule cigarettes would attract beginners, 10 and research in Mexico, with adolescents found to be more interested in trying cigarettes with capsules than without them. 9 With innovation fundamental to value growth for tobacco companies and younger people most receptive to such innovation, 18 the capsule segment has been a welcome success story for tobacco companies.…”
Section: Yum That Is Not Going To Help Me Quit (16-17 Female C2de)mentioning
confidence: 99%
“…This is perhaps most obvious with regards tobacco taxation and pricing, which are becoming increasingly important issues for tobacco companies in the UK (Gilmore 2012). For example, whilst virtually all tobacco interests tend prefer low tobacco taxes, and often lobby collectively on this issue , evidence suggests transnational tobacco companies may support tax increases if, for example, they believe this will help them achieve changes to tax structures which competitively favour their brands (Shirane et al 2012).…”
Section: Pfizer Ltd 2008mentioning
confidence: 99%
“…Although price increases are a powerful policy lever and reduce overall tobacco consumption, tobacco's addictive nature means even excise tax increases fail to stimulate quitting among many smokers 9 10. Furthermore, smokers can mitigate the impact of tax increases by smoking fewer cigarettes or trading down to less expensive brands, thus modest, regular price increases may have reduced impact over time 11.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, smokers can mitigate the impact of tax increases by smoking fewer cigarettes or trading down to less expensive brands, thus modest, regular price increases may have reduced impact over time 11. Excise tax increases also enable tobacco companies to manipulate prices; for example, by increasing the price of premium brands beyond the tax increase to enhance profits and subsidise budget brands 9 12. Evidence that smokers adapt to predictable price increases, while the tobacco industry uses these to enhance profitability, suggests multifaceted tobacco control strategies, including standardised packaging, are required to reduce smoking prevalence.…”
Section: Introductionmentioning
confidence: 99%